Gossip and coping with social isolation: the case of migrant truck drivers in Western Europe - Martinescu, Elena; Beersma, Bianca (Frontiers in Psychology, 2024)
This article examines how employees use gossip as a resource to cope with social isolation.Building on a qualitative study with 32 truck drivers in a Western European company, our research identified gossip in close relationships and gossip in distant relationships as distinct patterns playing a different role in coping with social isolation, and a third pattern in which gossip was not beneficial. First, gossiping with close friends at work helped drivers engage in emotion-focused coping by reducing stress and loneliness. Second, gossiping with distant colleagues helped drivers engage in problem-focused coping by exchanging knowledge involving people in the organization. Third, gossip avoidance occurred in distant relationships, where drivers limited gossip exchanges going beyond instrumentally useful information. Overall, these findings show that drivers relied on different layers of their social network to cope with social isolation. Enriching previous research, this study shows that gossip represents an essential resource for emotion-focused and problem-focused coping.